Fabrication of poly (vinyl alcohol)/Argenome mexicana extract composite nanofibers by electrospinning for antifungal and antimicrobial exploits - Manivannan Madhaiyan; Sathiya Nathan Selvam; Prasath Manivannan; Kamaraj Sattu; Dharmaraj Nallasamy; Prabu Periyasamy (Chemical Physics Impact)
Argenome mexicana (AM) is used in traditional chinese medicine. Isoquinoline alkaloids, such as berberine, coptisine, palmatine and magnoflorine are the primary active ingredients in AM; these compounds exhibit several pharmacological properties. Poly (vinyl alcohol) (PVA), a synthetic biocompatible polymer is widely utilised in food, pharmaceutical, cosmetic and packaging sectors. PVA can also be utilised as a matrix to incorporate functional components. In this study, the impact of AM extract concentrations on the morphologies, as well as the antibacterial and antifungal capabilities of PVA/AM extract composite nanofibers were investigated. FT-IR, XRD, SEM, TGA and cytotoxicity study were among the characterisation methods used. The antibacterial and antifungal potential of these nanofibers were assessed against Staphylococcus aureus and Staphylococcus epidermidis. Cytotoxicity of the fabricated composite nanofibers carried out fibroblast cells (NIH 3T3), no cytotoxic effects were observed.